ISLAMIC EDUCATION IN THE ERA OF DIGITALIZATION 5.0 - Mas'ula, Wahibatul; Hakim, Ahmad Muzakki (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Islamic Education in the Digitalization Era is a very important topic in the world of education today. With the rapid development of technology, the world of education must also adapt to these changes. The purpose of this research is to find out how Islamic education is implemented in the digitalization era, and its impact on student learning. The methods used in this research are case studies and surveys. The results of the study show that the implementation of Islamic education in the digitalization era can increase the effectiveness of student learning and increase student interest in learning. However, there needs to be supervision and regulation from the school in the use of technology so as not to have a negative impact.